Se, I, Fe, and Zn supply in population of various ecological regions of the Republic of Belarus with high incidence of thyroid disorders - Petrenko, Seregej V.; Leushev, Boris Yu.; Guliaeva, Ludmila S.; Nikitin, Dmitrij A.; Laptionok, Sergej A. (Journal of the Belarusian State University. Ecology, 2019)
Regardless conducted preventive measures aimed at iodine deficiency elimination in Belarus, we have found that iodine concentration in the bodies of schoolchildren from Brest region in 2018 is the lowest one comparing to the other regions of the country. Iodine excretion with urine (ioduria) in the considered region is 117.0 μg / l, at that national index is equal to 191.3 μg / l. Iodine deficiency prevalence i.e. distribution of children with inadequate iodine concentration in the body (less than 100 μg / l) is 39.9 %, and this national index is 25.9 %. The reason of such situation could be explained by the fact thatonly 33.1 % of examined children use iodized salt. Prevalence of simple goiter is 11.2 %, at that the national index is 8.5 %. Sonographic signs of autoimmune thyroiditis were recorded in 22 % of schoolchildren and 20 % of pregnant women from the town of Bereza, where only 22 % of schoolchildren and 36 % of pregnant women used iodized salt. Iodine concentration in the children bodies from orphanage school of the town of Telekhany was even lower. Median value of iodine excretion in urine there was 97.2 μg / l, goiter was recorded in 14.4 %, signs of autoimmune thyroiditis was found in 12.9 % of children, and prevalence of iodine deficiency was 54 %. Iodine concentration in the body is regulated by the amount of iodized salt intake, and to less extend by other foodstuffs. Concentration of I, Se, Zn and Fe in milk from private courtyards in the town of Bereza (Brest region) was lower by 58,5; 40; 7,5 and 19.7 %, correspondingly. In the hair of schoolchildren from the town of Bereza decreased concentration of Zn by 31.4 % and Se by 61.7 % was recorded. Fe concentration was in norm range.
Keywords: iodine excretion median; goiter; children; pregnant women